(untitled) (Actualizaciones en Sida e Infectología, 2021)
Rectal lymphogranuloma venereum: an emergent clinical presentation Abstract Lymphogranuloma venereum is a rare sexually transmitted infection (STI) caused by serotypes L1, L2 and L3 of Chlamydia trachomatis. For over a decade, there has been a considerable increase in the incidence of LGV proctitis in almost exclusively men who have sex with men with STI risk behaviors. Four cases of rectal LGV are reported.